Intensity: A Collaborative Autoethnography. Issue 1 (May 2013) - Gale, Ken; Pelias, Ron; Russell, Larry; Spry, Tami; Wyatt, Jonathan
In this collaborative autoethnography, the five of us explore the experience and ethics of writing—and living—from/in intensity. We have been writing together since meeting at the Third International Congress of Qualitative Inquiry (QI), when we made a commitment to write over the following year to, for, and with each other. It became an experiment in the craft of autoethnography, exploring questions of intimacy and connection manifested through collaborative writing, a series of texts exchanged via e-mail. This essay's sequence of writing during July and August 2008 follows a period of silence. Senses of intensities emerged from our collaborative autoethnographic practice over this period: We remain unsure of what intensities might be, and in the fluidity of this lack of certainty we feel we can claim a pedagogical practice of inquiry that comes from this writing into our always not-yet-known.